Sustainability of tropical animal-agricultural production systems: integration of dynamic complex systems - Ismail, Dahlan (2002)
Animal agriculture will remain critically important despite its declining relative contribution to the national economy. Demand form animal products will increase with better economic status of most developing countries. However as input sources of land, feed resources and labor become increasingly scarce for animal-agricultural production, new technologies will be required to improve the efficiency of the production systems. A more sustainable agriculture would be in tune with the local resource base, make maximum use of internal production inputs, and have potential for sustained production and bring benefit into the future. The new millennium approach for animal-agricultural production systems in most of tropical or developing countries in the world must be based on an integrated approach. Systems analysis is the methodology to be used to evaluate and plan for the future development of integrated productions systems. This methodology applies a holistic approach and considers multi-disciplines and multi-components in complex agricultural production systems